Peran Mahkamah Konstitusi dalam Proses Penyelesaian Pemilu Terkait Hasil Pemilu - Ferselli, Aurellia Karin; Azahra, Natasya Sabrina; Rasji, Rasji (Jurnal Ilmiah Wahana Pendidikan, 2024)
In accordance with the ruling of the Constitutional Court under Decision Number 97/PUU-XI/2013, the Constitutional Court no longer holds the authority to adjudicate disputes concerning the outcomes of direct local elections, as the provisions of Article 236C of Law Number 12 of 2008 are inconsistent with the 1945 Constitution of the Republic of Indonesia. Article 157 paragraph (1) of Law Number 8 of 2015 specifies that the resolution of disputes over regional election results falls directly within the purview of a specialized judicial entity. However, prior to the establishment of such a specialized judicial entity, the Constitutional Court retained the authority to adjudicate disputes over the outcomes of direct regional elections. The authority of the Constitutional Court is a temporary constitutional mandate to address legal vacuums. Hence, lawmakers must promptly establish a specialized judicial entity endowed with the authority to resolve disputes over the outcomes of direct regional elections.